PREVALENCE AND ANTIMICROBIAL SUSCEPTIBILITY OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS AND COAGULASE-NEGATIVE STAPHYLOCOCCI IN A TERTIARY CARE HOSPITAL. - MIR, BILAL AHMAD; ., Srikanth (Asian Journal of Pharmaceutical and Clinical Research, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: Globally nosocomial infection is a major problem. Prevalence and antibiotic resistance of methicillin-resistant Staphylococcus aureus (MRSA) strains is reported to be increasing globally. MRSA and methicillin resistant coagulase negative staphylococci (MRCoNS) are the important agents causing nosocomial infections. Objective: The study was conducted to find out the prevalence rate of MRSA and MRCoNS and antibiotic susceptibility pattern. Materials and Methods: This was a retrospective study conducted from June 2011 to November 2012 in a tertiary care hospital in south India. All isolates were identified by Clinical and Laboratory Standards Institute (CLSI) guidelines and antibiotic susceptibility pattern determined by modified Kirby Bauer disc diffusion method. The information was recorded and analyzed using Microsoft Excel (2007 version). Results: A total of 210 Staphylococcus strains were isolated from various clinical samples, 180 were coagulase positive staphylococcus (CoPS) and 30 were coagulase negative staphylococcus (CoNS). Among 180 CoPS, 58 (32.22%) were Methicillin resistant and among CoNS, 12 (40%) were methicillin resistant. In MRSA maximum resistance was seen with oxacillin (93.2%) and least with vancomycin (3.5%). In MRCoNS maximum resistance was seen with oxacillin (91.7%) and least with vancomycin (0 %). Conclusion: There is need for continuous monitoring of the antimicrobial susceptibility pattern of methicillin staphylococcus aureus and methicillin resistant coagulase negative staphylococci for the selection of appropriate therapy, developing the antibiotic policy and for limiting the use of powerful antibiotics. Key words: Methicillin-resistant Staphylococcus aureus (MRSA), Methicillin resistant coagulase negative staphylococci, Vancomycin, Nosocomial infection, Susceptibility pattern<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>